2016
DOI: 10.1016/j.urology.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Analysis of Perioperative Outcomes in Morbidly Obese Patients Following Renal Mass Surgery

Abstract: Morbid obesity (BMI ≥ 40) is an independent predictor of developing SSIs following renal mass surgery. Morbid obesity is not predictive of risk for major complications, receipt of PBT, hospital readmission, perioperative death, or LOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Studies of urologic procedures evaluating the association between BMI and surgical complications have shown that BMI is associated with a higher risk of overall complications in pediatric patients undergoing surgery (with a greater than 2fold increased odds of wound complications) and that a BMI of ≥40 kg/m 2 predicted surgical site infections in patients undergoing surgery for renal masses. 10,11 In other surgical populations, obesity has similarly been found to be linked to increased risk of complications. Obesity has been linked to wound complications and prolonged hospital stay in ovarian cancer patients, an increased risk of overall surgical morbidity in endometrial cancer patients, an increased risk of developing a hospital-acquired condition in adult spinal deformity patients, and an increased risk of wound and respiratory complications in intestinal surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of urologic procedures evaluating the association between BMI and surgical complications have shown that BMI is associated with a higher risk of overall complications in pediatric patients undergoing surgery (with a greater than 2fold increased odds of wound complications) and that a BMI of ≥40 kg/m 2 predicted surgical site infections in patients undergoing surgery for renal masses. 10,11 In other surgical populations, obesity has similarly been found to be linked to increased risk of complications. Obesity has been linked to wound complications and prolonged hospital stay in ovarian cancer patients, an increased risk of overall surgical morbidity in endometrial cancer patients, an increased risk of developing a hospital-acquired condition in adult spinal deformity patients, and an increased risk of wound and respiratory complications in intestinal surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike our study, previous studies focused on evaluating safety of minimally invasive surgical approach (laparoscopic or robotic partial nephrectomy) among obese patients and found no association between obesity and warm ischemia time ( 18 - 20 ). Obesity was associated with length of hospital study in a study of patients who underwent laparoscopic radical nephrectomy ( 24 ), but obesity was not associated with EBL or length of hospital stay in others studies of patient who underwent laparoscopic radical nephrectomy and studies including both nephrectomy types ( 22 , 23 , 41 , 42 ). In addition to potential differences in patients’ racial and ethnic and socioeconomic backgrounds, this study has several differences from previous studies.…”
Section: Discussionmentioning
confidence: 96%